Ubiquitin-specific protease 47 is associated with vascular calcification in chronic kidney disease by regulating osteogenic transdifferentiation of vascular smooth muscle cells - Qiong Xiao; Yun Tang; Juhua Xia; Haojun Luo; Meidie Yu; Sipei Chen; Wei Wang; Lei Pu; Li Wang; Guisen Li; Yi Li (Renal Failure, 2022)
Chronic kidney disease (CKD) has recently become a serious health and social concern. Vascular calcification, a common complication of CKD, is a risk factor that increases the incidence and mortality of cardiovascular events in patients with CKD. However, there are currently no effective therapeutic targets that can facilitate treatment with fewer side effects for vascular calcification in CKD. To identify potential therapeutic targets, we performed label-free quantification (LFQ) analyses of protein samples from rat aortic vascular smooth muscle cells (RASMCs) after high-phosphorus treatment by nano-UPLC–MS/MS. We determined that ubiquitin-specific protease 47 (USP47) may be associated with CKD vascular calcification by regulating the osteogenic transdifferentiation of the vascular smooth muscle cell (VSMC) phenotype, thus suggesting a novel and potentially effective therapeutic target for CKD vascular calcification. USP47 knockdown significantly reduced the expression of β-transducin repeat-containing protein (BTRC), serine/threonine-protein kinase akt-1 (AKT1), Klotho, fibroblast growth factor (FGF23), and matrix Gla protein (MGP) in RASMCs after high-phosphorus treatment. Consistent with the results of protein–protein interaction (PPI) analyses, USP47 may be involved in regulating osteogenic transdifferentiation markers, such as runt-related transcription factor 2 (RUNX2), Klotho, FGF23, and MGP through the BTRC/AKT1 pathway upon CKD vascular calcification. These data indicate that USP47 may be associated with vascular calcification in CKD by regulating osteogenic differentiation of VSMCs. USP47 may regulate osteogenic transdifferentiation in VSMCs upon CKD vascular calcification through a process involving the BTRC/AKT1 pathway. This study identified a novel potential therapeutic target for the treatment of vascular calcification in CKD.